Rimsulfuron uptake, translocation, metabolism and (2003)
Research was conducted to determine the role in selectivityof uptake, translocation, metabolism and ALS (acetolactatesynthase) activity of rimsulfuron in two maize (Zea maysL.) hybrids (‘Cargill 2127’, tolerant, and ‘Pioneer 3897’,sensitive) grown at temperatures of 14°C and 21°C. Fortyeight hours after treatment (HAT), uptake of rimsulfuronwas 40% and 67% in ‘Pioneer 3897’, and 26% and 43%in ‘Cargill 2127’ at 14°C and 21°C, respectively. Neithertotal translocation nor allocation of rimsulfuron in variousorgans differed greatly between the hybrids. Translocationof 14C-rimsulfuron was greater at 21°C (53%) than at 14°C(23%), 48 HAT. In ‘Pioneer 3897’ over 65% and 30% ofthe total 14C-activity present in plant extracts was recoveredas the parent compound within 24 HAT, at 14°C and21°C, respectively. However, in ‘Cargill 2127’ detoxificationof rimsulfuron was not affected by temperature, and27% of the 14C-total activity was recovered as the parentcompound. Crude ALS extracts from ‘Pioneer 3897’ and‘Cargill 2127’ maize seedlings were treated with variousdoses (0.001, 0.005, 0.01, 0.1 and 1.0 μM) of rimsulfuron.Based on ALS specific activity, I 50 values differed sligthlybetween the two hybrids (I 50 ‘Pioneer 3897’ = 0.091 μMand I 50 ‘Cargill 2127’ = 0.142 μM). These results suggestthat the mechanism of rimsulfuron tolerance in maizecould be mainly explained by differential herbicide uptakeand detoxification, with translocation and ALS sensitivityhaving little effect on differential tolerance of these maizehybrids to rimsulfuron. On the other hand, the greateruptake and translocation of rimsulfuron at 21°C, comparedto 14°C, could explain the observed herbicide injury inmaize at high temperatures under field conditions.